The night that finds us all - Jacobs, John Hornor (G. P. Putnam Sons, 2025)
"Sam Vines is struggling. Her boat is up on the hard and she doesn't have enough money to get her back in the water. Turns out the snorkelers and the scubadivers are looking for the ultra-luxury boating experience, not the single-handed, rarely sober, snarky stylings of sailboat captain Samantha Vines. So it's a good thing when her former crewmate Loick asks her to help deliver a massive, hundred-year-old sailboat from Seattle to England. Sam is the only one who can handle the ship's engine, and did Loick mention that the money is good? It's very good. The Blackwatch is a huge boat. An ancient boat. It's also probably (definitely) haunted. Someone's standing on deck, no wait, they're gone. Wet feet slap against the wood at night. Something screams, a wail that rises up through the rigging. Sam's alcohol withdrawal (sobriety is important at sea) has her doubting her senses, but when one crewmate disappears and another has a gruesome accident, she knows that this simple delivery job has spiraled into something sinister"--